The W-Acidic Motif of Histidine Kinase WalK Is Required for Signaling and Transcriptional Regulation in Streptococcus mutans - Kong, Lingyuan; Su, Mingyang; Sang, Jiayan; Huang, Shanshan; Wang, Min; Cai, Yongfei; Xie, Mingquan; Wu, Jun; Wang, Shida; Foster, Simon J.; Zhang, Jiaqin; Han, Aidong (Frontiers in Microbiology, 2022)
In Streptococcus mutans, we find that the histidine kinase WalK possesses the longest C-terminal tail (CTT) among all 14 TCSs and this tail plays a key role in the interaction of WalK with its response regulator WalR. We demonstrate that the intrinsically disordered CTT is characterized by a conserved tryptophan residue surrounded by acidic amino acids. Mutation in the tryptophan not only disrupts the stable interaction, but also impairs the efficient phosphotransferase and phosphatase activities of WalRK. In addition, the tryptophan is important for WalK to compete with DNA containing a WalR binding motif for the WalR interaction. We further show that the tryptophan is important for in vivo transcriptional regulation and bacterial biofilm formation by S. mutans. Moreover, Staphylococcus aureus WalK also has a characteristic CTT, albeit relatively shorter, with a conserved W-acidic motif, that is required for the WalRK interaction in vitro. Together, these data reveal that the W-acidic motif of WalK is indispensable for its interaction with WalR and signal transduction, and thereby for WalRK-dependent transcriptional regulation and biofilm formation.